Jejak Perjalanan Perkembangan Israiliyyat Dalam Penafsiran - Aisyiyyah, Lu'luatul; Fauzi, Muhammad Iqbal; Jamarudin, Ade (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2023)
This paper aims to analyze the journey of the development of Israiliyyat in interpretation so that many influences on understanding are produced from it. The method of writing this research is qualitative library research by describing the data obtained both from the main source and other sources. This paper argues that the Qur'an is a mu'jizat book revealed by Allah SWT to His Messenger, Prophet Muhammad SAW The miracle of the Qur'an is clearly seen from the beautiful language structure with many implied meanings. Apart from being a book of miracles, the Qur'an is also a book of guidance that is able to guide humans and especially people who believe in Allah SWT towards happiness in this world and in the hereafter. In understanding this book of guidance, the scholars and even the Companions at the time of the Prophet SAW mobilized all available scientific capacity, so that the function of the Qur'an as a book of guidance could be felt in life. The stories of Israiliyyat contribute to the understanding of the implementation of the interpretation of the Qur'an. The news brought by the Jews and Christians is certainly accepted by the process of filtering the history. The entry of Israiliyyat into tafsir and hadith went through two periods: the period of narration and the period of codification. These two periods are very influential on the development of Israiliyyat which is used as a reference source or complement to existing stories. There are some scholars who reject and accept the presence of Israiliyyat into the interpretation, especially those who reject the view that Israiliyyat is one of the superstitious infiltration efforts that can shake the authenticity of the Qur'an. As for those who accept it as a complementary reference to the stories that are only briefly mentioned in the Qur'an.